1993
DOI: 10.1093/nar/21.12.2945
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the human S13 ribosomal protein cDNA

Abstract: In a hope to isolate genes whose expression was elevated in colon cancer cells, we used a plus/minus screening of a rat colon carcinoma cDNA library. We were thus able to isolate a cDNA clone (B9) encoding the rat S13 ribosomal protein (1). The corresponding mRNA is-30-fold more abundant in the cancer cells than in normal colon, and 50-fold more important in lung metastasis than in normal lung. The expression level of this gene was found to be closely correlated with the growth rate of rat cell lines (1). Unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Necl-5/Tage4/poliovirus receptor (PVR)/CD155 is an immunoglobulin (Ig)-like molecule having a domain structure consisting of one extracellular region with three Ig-like loops, one transmembrane region, and one cytoplasmic region (Mendelsohn et al, 1989;Koike et al, 1990;Chadeneau et al, 1994Chadeneau et al, , 1996. Human PVR/ CD155 was originally identified as the human PVR (Mendelsohn et al, 1989;Koike et al, 1990), whereas Tage4 was originally identified as the product of a gene overexpressed in rat and mouse colon carcinoma (Chadeneau et al, 1994(Chadeneau et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Necl-5/Tage4/poliovirus receptor (PVR)/CD155 is an immunoglobulin (Ig)-like molecule having a domain structure consisting of one extracellular region with three Ig-like loops, one transmembrane region, and one cytoplasmic region (Mendelsohn et al, 1989;Koike et al, 1990;Chadeneau et al, 1994Chadeneau et al, , 1996. Human PVR/ CD155 was originally identified as the human PVR (Mendelsohn et al, 1989;Koike et al, 1990), whereas Tage4 was originally identified as the product of a gene overexpressed in rat and mouse colon carcinoma (Chadeneau et al, 1994(Chadeneau et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Human PVR/ CD155 was originally identified as the human PVR (Mendelsohn et al, 1989;Koike et al, 1990), whereas Tage4 was originally identified as the product of a gene overexpressed in rat and mouse colon carcinoma (Chadeneau et al, 1994(Chadeneau et al, , 1996. PVR/CD155 has subsequently been shown to be overexpressed in human colorectal carcinoma and malignant glioma (Gromeier et al, 2000;Masson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These include Necl-1/ TSLL1/SynCAM3 (16,17), Necl-2/IGSF4/RA175/SgIGSF/ TSLC1/SynCAM1 (17-21), Necl-3/similar to NECL3/SynCAM2 (17), Necl-4/TSLL2/SynCAM4 (16,17), and Necl-5/Tage4/human poliovirus receptor (PVR)/CD155 (22)(23)(24)(25). The domain structures of this group of molecules are similar to those of nectins, but they do not bind afadin (11,26).…”
mentioning
confidence: 99%
“…Tage4 was originally identified to be the product of a gene overexpressed in rat and mouse colon carcinoma (24,25). The Tage4 gene has been mapped to rat chromosome 1q22 (27) and mouse 7A2-B1 (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation